Pipeline Power - Franz Hubert; Onur Cobanli (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We use cooperative game theory to analyze the impact of three controversial pipeline projects on the power structure in the Eurasian trade of natural gas. Two of them, Nord Stream and South Stream, allow Russian gas to bypass transit countries, Ukraine and Belarus. Nord Stream's strategic value turns out to be huge, justifying the high investment cost for Germany and Russia. The additional leverage obtained through South Stream, in contrast, appears small. The third project, Nabucco, aims at diversifying Europe's gas imports by accessing producers in Middle East and Central Asia. It curtails Russia's power, but the benefits accrue mainly to Turkey, while the gains for the EU are negligible.
Keywords: L5; L9; O22; 330; Bargaining Power; Network; Trade links; Natural Gas; Erdgas; Gasversorgung; Erdgaspolitik; Kooperatives Spiel; Russland; Westeuropa